VANET security surveys - Engoulou, Richard Gilles; Bellaïche, Martine; Pierre, Samuel; Quintero, Alejandro (Computer communications, 2014)
Vehicular ad hoc networks (VANETs), a subset of Mobile Ad hoc NETworks (MANETs), refer to a set of smart vehicles used on the road. These vehicles provide communication services among one another or with Road Side Infrastructure (RSU) based on wireless Local Area Network (LAN) technologies. The main benefits of VANETs are that they enhance road safety and vehicle security while protecting drivers’ privacy from attacks perpetrated by adversaries. Security is one of the most critical issues related to VANETs since the information transmitted is distributed in an open access environment. VANETs face many challenges. This paper presents a survey of the security issues and the challenges they generate. The various categories of applications in VANETs are introduced, as well as some security requirements, threats and certain architectures are proposed to solve the security problem. Finally, global security architecture for VANETs is proposed.